Antigen-specificity measurements are the key to understanding T cell responses - Tippalagama, Rashmi; Chihab, Leila Y.; Kearns, Kendall; Lewis, Sloan; Panda, Sudhasini; Willemsen, Lisa; Burel, Julie G.; Lindestam Arlehamn, Cecilia S. (Frontiers in Immunology, 2023)
Antigen-specific T cells play a central role in the adaptive immune response and come in a wide range of phenotypes. T cell receptors (TCRs) mediate the antigen-specificities found in T cells. Importantly, high-throughput TCR sequencing provides a fingerprint which allows tracking of specific T cells and their clonal expansion in response to particular antigens. As a result, many studies have leveraged TCR sequencing in an attempt to elucidate the role of antigen-specific T cells in various contexts. Here, we discuss the published approaches to studying antigen-specific T cells and their specific TCR repertoire. Further, we discuss how these methods have been applied to study the TCR repertoire in various diseases to characterize the antigen-specific T cells involved in the immune control of disease.